Benralizumab for the add-on maintenance treatment of patients with severe asthma aged 12 years and older with an eosinophilic phenotype. Issue 7 (3rd July 2018) - Al Efraij, Khalid; FitzGerald, J. Mark
ABSTRACT: Introduction : Asthma is an airway disease characterized by airway inflammation. It is associated with significant morbidity, mortality, and costs to the health-care system and society. Eosinophils and interleukin-5 (IL-5) play a key role in the inflammatory response in T-helper 2-high asthma. IL-5 is pivotal for eosinophil development, maturation, and survival in tissues. Asthma severity has been related to both airway and peripheral blood eosinophilia. Areas covered : In this review, we present the pharmacokinetics and pharmacodynamics of benralizumab in addition to efficacy and safety data in the treatment of severe eosinophilic asthma. Expert commentary : Benralizumab is a potent biologic targeting the IL-5 receptor on eosinophils and basophils leading to depletion of target cells in peripheral blood and tissues. It is effective in reducing asthma exacerbations and has an oral corticosteroid-sparing effect in the treatment of asthma patients who are not controlled with medium-to-high-dose inhaled corticosteroids and long-acting beta agonists. The side effect profile is similar to placebo with the most reported adverse events being nasopharyngitis and worsened asthma in the pivotal trials. Its long-term safety is currently under investigation.